Amorphous cellulose electrolyte for long life and mechanically robust aqueous structural batteries - Lim, Gwendolyn Jia Hao (2024)
Aqueous zinc (Zn)-based structural batteries capable of both electrochemical energy storage and mechanical load-bearing capabilities are attractive for next-generation energy storage for future electric vehicles due to their eco-friendliness, non-toxic, and safe nature. However, parasitic free water activities plague aqueous Zn-based batteries, detrimental to the electrochemical performance and longevity of the cell. Developing polymer gel electrolytes is a notable potential solution, but they usually have poor electrode interfacial interactions and inadequate mechanical properties. This article introduces a novel non-fibrous highly amorphous cellulose polymer electrolyte “Cellyte” for aqueous structural Zn-based batteries. Cellyte exhibits a high strength of ≈24 MPa and Young's modulus of ≈380 MPa, along with the ability to suppress parasitic water activity. The symmetric Zn||Cellyte||Zn cell therefore demonstrates excellent cycling stability of over ≈3000 h. Cellyte can also serve as the binder for the structural cathode material, creating a continuous polymer electrolyte–cathode interface, thereby increasing mechanical robustness and decreasing interfacial resistances of the battery, allowing the structural Zn||Cellyte||LMO-CF battery to achieve high electrochemical performance with excellent cycling stability over 1200 h with ≈91.5% capacity retention. This provides a pathway to design mechanically robust, electrochemically performing, and safe structural batteries.